Diseño y construcción de un tablero didáctico para instalación de un sistema de seguridad electrónico. - Cango Chamba, Romel Marcelo (2010)
Electronic Security Systems are increasingly widespread due to the need for greater security; With the emergence of electronics has allowed us to make rapid progress in security since it provides us with a variety of possibilities as regards electronic security systems. An electronic security system can be defined as the set of elements and facilities necessary for To provide people and material goods in a particular place with protection such as theft, robbery, fire, etc. The electronic security systems can be of different types according to the need of the place to protect and the budget available for the assembly. Therefore, the present project that is detailed below is destined to the students of professional formation of the Race of Technology Electrical and in general who interested in the subject. With the same intent provide a broader view of new technological advances; And in particular to the installation and basic programming of an Electronic Security System as it is of great importance and of interest to each and every one of the students of the Electrical Technology Career. In addition to the high level of insecurity at the local level as national forces certain establishments such as banks, jewelers, factories, warehouses, homes, etc. To have security systems of the place to be protected. The subject of Electronic Security aims to provide information to the students of the Electrical Technology Career of the National University of Loja through a didactic board to have theoretical and practical knowledge of what is the installation of an alarm system; At the same time acquire skills and technical-practical skills to connect and program the basic equipment used for such installation and thus achieve significant learning. In this way combining a good alarm system with other security measures, serve as an important contribution to the Electrical Workshop and especially the students to have a clear and correct idea of the activation and deactivation of an alarm